Mind the Gap: Dealing with Resource Revenue in Three Provinces - Ronald D. Kneebone (The School of Public Policy Publications, 2015)
Alberta, Saskatchewan, Newfoundland and Labrador have each enjoyed a “rags to riches” story. Each of these provinces entered Confederation as poor cousins relative to the rest of the country; Alberta and Saskatchewan in 1905 and Newfoundland and Labrador in 1949. Rather remarkably, almost exactly four decades after entering Confederation each province began to enjoy the strong economic growth resulting from the development of their natural resources; Alberta and Saskatchewan in the late 1940s with the discovery of large pools of oil and Newfoundland and Labrador in the early 1990s with the development of off-shore oil. The governments of these provinces have similarly enjoyed the benefits of large amounts of revenue realized from the sale of these natural resources. In 2013-14, resource revenues accounted for 21 per cent, 22 per cent and 32 per cent of provincial revenues in Alberta, Saskatchewan, Newfoundland and Labrador, respectively. Unfortunately, the benefit of receiving large amounts of resource revenue must be weighed against two costs. The first is that these revenues, having flowed into provincial coffers without the need to impose high tax rates on citizens, are easily spent. The second cost is that the prices of resources are determined in international markets and so a significant amount of the revenues of these provinces is largely unpredictable and often volatile. All three provinces have fallen prey to the temptation to allow a large fiscal gap to open between the costs of providing health care, education, social assistance and other areas of provincial responsibility and the taxes imposed on citizens to pay for these services. Doing so has put all three provinces at financial risk should resource prices fall. Using a newly constructed data set spanning the period 1970 to 2014, I review the history of how Alberta and Saskatchewan have dealt with commodity price shocks and what this has meant for provincial finances. With that history as background, I review the response of the government of Newfoundland and Labrador to the flood of revenue it has received over the past decade as a result of the development of off-shore oil fields. The evidence is clear that Newfoundland and Labrador has adopted the same high-risk budgeting strategy as Alberta and Saskatchewan; a strategy that has seen the province choose to fund health care, education and social assistance using revenues that are unreliable and unpredictable. As Newfoundland and Labrador prepares for the release of its budget for 2015-16, it must begin to deal with the effect on its revenues of a dramatic fall in oil prices, a historically large budget deficit and a threat to the financial viability of its health, education and social assistance programs.